Application of quality tools in a service provider company: a bibliometric analysis through Proknow-c - Nascimento, Amanda Assunção; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2022)
Quality management is progressively more present in-service providers, since currently delivering a quality service to the final customer is becoming a requirement on the part of consumers in general. This implies that it is extremely important for a company to remain in the market through an adequate standard and, for that, quality tools were developed to help improve services, in addition to finding adequate solutions to the problems that arise. in organizations. Thus, the present study has as main objective to analyze the bibliographic portfolio found through the ProKnow-C method, which brings relevant articles in relation to the following topic: Application of quality tools in a service provider company. The ProKnow-C method refers to a quantitative analysis of published articles in relation to the search and selection process. From this study, 16 articles were identified that constitute the bibliographic portfolio, where they were observed in these works, the means in which they were published, the material that served as support for the works, in addition to their contributions with regard to the results of the articles in relation to the application of quality tools.
Keywords: Quality; Service sector; ProKnow-C; tools